Tipologija ženskih oseb v pripovedni prozi avtorjev druge polovice 19. stoletja - Rebol Kotnik, Alenka (Jezik in slovstvo, 2007)
In narrative prose by authors from the second half of the nineteenth century, females can generally be categorised according to their character, function and appearance, into four basic types: the type of a mother, a daughter, a wife or an unwedded partner, and the type of an aunt, a friend, a distant relative, or an unknown woman. For a more accurate and complex presentation offemale characters they can be further categorized into various sub-types. Within this typology a woman appears as a two-fold person: on the one hand, the image of a typically unselfish, good, obedient and humble woman, and, on the other hand, an image of a completely different, stubborn, dominant, materialistic, egotistical, and even physically violent woman, by which the author rejects the general, exclusively stereotypical image of the literary female character of the past.
Keywords: pripovedna proza; Slovene literature; slovenska književnost; tipologija; ženski liki; žensko vprašanje